Study of the Mechanisms of Internal Short Circuit in a Li/Li Cell by Synchrotron X-ray Phase Contrast Tomography - Sun, Fu; Moroni, Riko; Dong, Kang; Markeotter, Henning; Zhou, Dong; Hilger, Andre; Zielke, Lukas; Zengerle, Roland; Thiele, Simon; Banhart, John; Manke, Ingo (ACS Energy Letters, 2017)
Knowledge about degradation and failure of Li-ion batteries (LIBs) is of paramount importance, especially because failure can be accompanied by severe hazards. To contribute to the understanding of such phenomena, synchrotron in-line phase contrast X-ray tomography was employed to investigate internal cell deformation and degradation caused by an internal short circuit (ISC). The tomographic images taken from an uncycled Li/Li cell and a short-circuited Li/Li cell reveal how lithium microstructures (LmSs) develop during electrochemical stripping and plating during discharge and charge and how the three-layer separator used is damaged by growing LmSs and delaminates and melts as a consequence of an ISC. Previously unknown insights into the internal cell degradation and deformation mechanisms caused by an ISC are obtained and provide hints of how the properties of the separator could be modified to improve the reliability and safety of current- and next-generation LIBs.
CRIS-Team Scopus Importer:2023-03-29